Development and quality evaluation of thermally processed jackfruit (Artocarpus heterophyllus L.) - PRITTY S. BABU; Dr. Sudheer K. P (Guide) (Tavanur 2012 Department of Post-Harvest Technology and Agricultural Processing)
seasonal fruit - varikka jackfruit - brine, citric acid and KMS
Development and quality evaluation of thermally processed jackfruit (Artocarpus heterophyllus L.)